TINJAUAN PENYEBAB KERUSAKAN DOKUMEN REKAM MEDIS BAGIAN FILING DI RUMAH SAKIT BMC MAYAPADA - Nia Nurhasanah,; Yuyun Yunengsih, (Journal of Innovation Research and Knowledge, 2021)
Medical record is a file that contains records and files regarding patient identity,examination results, treatment, actions and other services that have been provided to patients. Medical Record Documents (DRM) must be managed properly, because they have great value for the hospital. In its management, storage, security and maintenance efforts are needed so that it does not get damaged quickly. The purpose of this study was to determine the causes of the damage factors of Medical Record Documents in the Filing section of BMC Mayapada Hospital. with this type of qualitative research with data collection methods by observation and interviews. Based on the results of a study conducted at BMC Mayapada Hospital, the authors took a random sampling of 100 Medical Record Documents (taken at random) and found 20 damaged Medical Record Documents. After observing this damaged Medical Record Document, because the average document thickness is above 5cm, the storage rack is too full even though retention has been carried out every year, Medical record documents are located on shelves far from ventilation and sunlight causing documents to be moist and easily torn and the humidity factor of the room temperature even though the room maintenance has been carried out by spraying termites and insects periodically.